2004
DOI: 10.1128/aem.70.4.2332-2341.2004
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen-Controlled Bacterial Growth in the Sponge Suberites domuncula : toward a Molecular Understanding of the Symbiotic Relationships between Sponge and Bacteria

Abstract: Sponges (phylum Porifera), known to be the richest producers among the metazoans of bioactive secondary metabolites, are assumed to live in a symbiotic relationship with microorganisms, especially bacteria. Until now, the molecular basis of the mutual symbiosis, the exchange of metabolites for the benefit of the other partner, has not been understood. We show with the demosponge Suberites domuncula as a model that the sponge expresses under optimal aeration conditions the enzyme tyrosinase, which synthesizes d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 52 publications
1
24
0
Order By: Relevance
“…The bacterium can obtain protocatechuate in situ from the sponge, which produces this and other diphenols via the activities of the enzyme tyrosinase. Interestingly, tyrosinase activity and expression of the tyrosinase-encoding gene in S. domuncula, as well as the number of pcaDC genes in strain SB2 (responsible for bacterial utilization of protocatechuate and used here as a proxy for SB2 abundance on the surface [exopinacoderm] of the sponge), were all maximal under aerated conditions (241). Coupled with the observed loss of SB2 cells from the sponge surface under low-oxygen conditions, it was asserted that the oxygen level is responsible for regulating the bacterial fauna in sponges.…”
Section: Ecological Aspects: From Single Cells To the Global Scale Esmentioning
confidence: 95%
See 2 more Smart Citations
“…The bacterium can obtain protocatechuate in situ from the sponge, which produces this and other diphenols via the activities of the enzyme tyrosinase. Interestingly, tyrosinase activity and expression of the tyrosinase-encoding gene in S. domuncula, as well as the number of pcaDC genes in strain SB2 (responsible for bacterial utilization of protocatechuate and used here as a proxy for SB2 abundance on the surface [exopinacoderm] of the sponge), were all maximal under aerated conditions (241). Coupled with the observed loss of SB2 cells from the sponge surface under low-oxygen conditions, it was asserted that the oxygen level is responsible for regulating the bacterial fauna in sponges.…”
Section: Ecological Aspects: From Single Cells To the Global Scale Esmentioning
confidence: 95%
“…In another recent study from the Müller group, using S. domuncula and its alphaproteobacterial symbiont SB2 as a model system, the importance of oxygenation of sponge tissue in mediating the relationship was demonstrated (241). Specifically, it was shown that strain SB2 grew preferentially on minimal media with the aromatic compound protocatechuate, rather than glucose, as the carbon source.…”
Section: Ecological Aspects: From Single Cells To the Global Scale Esmentioning
confidence: 99%
See 1 more Smart Citation
“…The establishment of this relationship relies on mutual recognition between the sponge and its microbial partners, and also on physical competition among the microbial communities themselves (Wilkinson 1984, Müller & Müller 2003, Müller et al 2004). In accordance with this hypothesis, sponges inhabiting the same ecological niche tend to harbor similar microbial communities.…”
Section: Abstract: Sponge · Bacterial Diversity · Community Compositmentioning
confidence: 99%
“…These mixtures were separated and the ethyl acetate layers were evaporated using rotary evaporator at 40°C. The extracts were vacuumed and stored below 5°C for further test (Muller et al, 2004).…”
Section: Extraction Of Bioactive Compounds From Bacteriamentioning
confidence: 99%